APLIKASI MOBILE PEMBUKTIAN KUNJUNGAN MEDICAL REPRESENTATIVE DI PT.GUARDIAN PHARMATAMA MENGGUNAKAN METODE MOBILE DEVELOPMENT - Wibowo, Sidik Harto; Wahyu, Sawali (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
PT. Guardian Pharmatama is a sizable pharmaceutical firm that has created numerous drug brands. All corporate operations have been carried out in a contemporary manner, so technology has no place in them. PT. Guardian Pharmatama places a lot of emphasis on product offerings and sales methods, similar to other businesses in general, especially for workers who work as medical representatives (abbreviated Medrep or Sales in the pharmaceutical sector). Visits to outlets (hospitals and pharmacies) are how Medrep strives to educate and promote its goods. In reality, however, because it is merely a written report, Medrep has not been able to offer genuine proof of having visited the business. In order to prove that Medrep visited, a system of proof is needed. This proof system will take the form of an application with a tracking feature, a photo upload feature, and an Android-based location point. This application was created using the Mobile-D technique, which was created specifically for building Android mobile applications. With the creation of this application, it is hoped that the sales and marketing divisions will be able to carry out their tasks more efficiently and methodically, the area manager will gain clarity regarding the proof of visits by Medrep staff, and they will be able to assist Medrep staff in creating visit reports.